Elevated Neurokinin-1 Receptor Expression in Uterine Products of Conception Is Associated With First Trimester Miscarriages - Alwazzan, Ahmad; Mehboob, Riffat; Hassan, Amber; Perveen, Shahida; Sadaf,; Gilani, Syed Amir; Ahmad, Fridoon Jawad; Tanvir, Imrana; Babar, Masroor Elahi; Tariq, Muhammad Akram; Ali, Gibran; Akram, Shehla Javed; et al. (Frontiers in Physiology, 2020)
Miscarriage is a common complication of early pregnancy, mostly occurring in first trimester. However, the etiological factors, prognostic and diagnostic biomarkers are not well known. Neurokinin-1 Receptor (NK-1R) is a receptor of tachykinin peptide, Substance P (SP) and has a role in various pathological conditions, cancers but it’s association with miscarriages and significance as a clinicopathological parameter is not studied. Accordingly, the present study aimed to clarify the localization and expression for NK-1R in human retained products of conception. Materials and Methods: NK-1R expression was assessed in products of conception and normal placental tissues by immunohistochemistry. 3-4µm thin sections of formalin fixed paraffin embedded tissues were used for this purpose. Tissues were processed and then immunohistochemically stained with NK-1R antibody. Brain tissue was used as control for antibody. Protein expression was evaluated using the nuclear labelling index (%). Tissues were counterstained with DAB and microscopy was performed at 10,20 and 40 X magnifications. Results: Ten human products of conception tissues and ten normal placental tissues were studied by immunohistochemistry to demonstrate the localization of NK-1R. The expression of NK-1R protein was high in all the cases of both groups. NK-1R expression showed no notable differences among different cases of miscarriages as well as normal deliveries at full term irrespective of the mother’s age and gestational age at which the event occurred. Statistically no difference was found in both the groups which is in agreement with our hypothesis and previous findings. Conclusions: Expression of NK-1R was similar in all the cases and it was intense. It shows that dysregulation of NK-1R along with its ligand Substance P might be involved in miscarriages and also involved in normal delivery. Our results provide fundamental data regarding this anti-NK-1R strategy. Thus, the present study recommends that SP/NK-1R system might, therefore, be considered as an emerging and promising diagnostic and therapeutic strategy against miscarriages. Hence, we report for the first time, the expression and localization of NK-1R in products of conception. We suggest NK-1R antagonist in addition to the Immunoglobulins and Human chorionic gonadotropin, to diagnose and treat spontaneous miscarriages.